Neutrophil extracellular traps drive epithelial–mesenchymal transition of human colon cancer. Issue 4 (15th February 2022) - Stehr, Antonia M; Wang, Guangxia; Demmler, Richard; Stemmler, Marc P; Krug, Julia; Tripal, Philipp; Schmid, Benjamin; Geppert, Carol I; Hartmann, Arndt; Muñoz, Luis E; Schoen, Janina; Völkl, Simon; et al.
Abstract: Neutrophil extracellular traps (NETs) are extracellular structures, composed of nuclear DNA and various proteins released from neutrophils. Evidence is growing that NETs exert manifold functions in infection, immunity and cancer. Recently, NETs have been detected in colorectal cancer (CRC) tissues, but their association with disease progression and putative functional impact on tumourigenesis remained elusive. Using high‐resolution stimulated emission depletion (STED) microscopy, we showed that citrullinated histone H3 (H3cit) is sufficient to specifically detect citrullinated NETs in colon cancer tissues. Among other evidence, this was supported by the close association of H3cit with de‐condensed extracellular DNA, the hallmark of NETs. Extracellular DNA was reliably differentiated from nuclear condensed DNA by staining with an anti‐DNA antibody, providing a novel and valuable tool to detect NETs in formalin‐fixed paraffin‐embedded tissues. Using these markers, the clinical association of NETs was investigated in a cohort of 85 patients with colon cancer. NETs were frequently detected (37/85, 44%) in colon cancer tissue sections and preferentially localised either only in the tumour centre or both in the tumour centre and the invasive front. Of note, citrullinated NETs were significantly associated with high histopathological tumour grades and lymph node metastasis. In vitro, purified NETs induced filopodia formation and cell motility in CRC cell lines. This was associated with increased expression of mesenchymal marker mRNAs (vimentin [ VIM ], fibronectin [ FN1 ]) and epithelial–mesenchymal transition promoting transcription factors ( ZEB1, Slug [ SNAI2 ]), as well as decreased expression of the epithelial markers E‐cadherin ( CDH1 ) and epithelial cell adhesion molecule ( EPCAM ). These findings indicated that NETs activate an epithelial–mesenchymal transition‐like process in CRC cells and may contribute to the metastatic progression of CRC. © 2021 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.